The Influence of Awareness of Taruna Coral Youth on the Mitigation of Longsor Land Disaster in the North Tapanuli Regency - Reinhard Simamora; Zulkifli Nasution; Agus Purwoko (Budapest International Research and Critics University, 2021)
North Tapanuli Regency is one of the districts in North Sumatra Province which is prone to landslides. Almost every year landslides are recorded in North Tapanuli Regency. This condition certainly must be responded to by both the government and the community to mitigate landslides. Youth groups from Taruna Coral have the potential with the demographic bonus of youth and the awareness they have to play a role in mitigating landslides. Therefore, this study wants to see how the awareness of Taruna Coral towards landslide mitigation in North Tapanuli Regency. This study uses a quantitative approach using tests and questionnaires as a measuring tool. The collected data were analyzed using multiple regression analysis techniques and the F test to see the effect of awareness of Taruna Coral on landslide disaster mitigation. The results showed that the awareness of Taruna Coral which consists of aspects of knowledge, attitudes, and behavior has a positive and significant effect on landslide disaster mitigation which includes prevention, preparedness, and countermeasures.